Produtividade primária fitoplanctônica submetida a diferentes qualidades espectrais da luz - Oliveira, Fabricio Bronzoni de (2020)
Knowledge about the primary productivity process is of fundamental importance for understanding the metabolism and energy dynamics in natural ecosystems. Thus, the present study aimed to analyze the effects of three wavelength bands (blue, green and red),